DJ‐1 Alleviates Angiotensin II‐Induced Endothelial Progenitor Cell Damage by Activating the PPARγ/HO‐1 Pathway. Issue 1 (7th July 2017) - Han, Tao; Liu, Meihan; Yang, Songbai
ABSTRACT: There is evidence that angiotensin II (Ang II) may impair the functions of endothelial progenitor cells (EPCs). It was revealed that DJ‐1 could resist oxidative stress. In this study, we investigated whether DJ‐1 could protect EPCs against Ang II‐induced cell damage. The proliferation and migration of EPCs were strongly reduced in the Ang II group and were increased by overexpression of DJ‐1. Western blotting indicated that the increased expression of the senescence marker β‐galactosidase and decreased expression of adhesion molecules (ICAM‐1, VCAM‐1) induced by Ang II were reversed after Ad‐DJ‐1 transfection. The reduced angiogenic capacity of EPCs caused by Ang II was also improved after Ad‐DJ‐1 transfection. Moreover, Ang II significantly increased the levels of reactive oxygen species (ROS), malondialdehyde (MDA), and inflammatory cytokines (TNF‐α and IL‐1β), reduced the levels of superoxide dismutase (SOD), glutathione (GSH), and these were reversed by Ad‐DJ‐1 transfection. Expression of peroxisome proliferator‐activated receptor‐γ (PPARγ) and heme oxygenase (HO‐1) was increased by DJ‐1. Therefore, HO‐1 siRNA were constructed and transfected into EPCs, and the results showed that HO‐1 siRNA transfection inhibited the effects of DJ‐1 on EPC function. Thus, our study implies that DJ‐1 may protect EPCs against Ang II‐induced dysfunction by activating the PPARγ/HO‐1. J. Cell. Biochem. 119: 392–400, 2018. © 2017 Wiley Periodicals, Inc. Abstract : Our study implies that DJ‐1 may protect EPCs against Ang II‐induced dysfunction by activating the PPARγ/HO‐1.